Integration of human stem cell-derived in vitro systems and mouse preclinical models identifies complex pathophysiologic mechanisms in retinal dystrophy - Jones, Melissa K.; Orozco, Luz D.; Qin, Han; Truong, Tom; Caplazi, Patrick; Elstrott, Justin; Modrusan, Zora; Chaney, Shawnta Y.; Jeanne, Marion (Frontiers in Cell and Developmental Biology, 2023)
Rare DRAM2 coding variants cause retinal dystrophy with early macular involvement via unknown mechanisms. We found that DRAM2 is ubiquitously expressed in the human eye and expression changes were observed in eyes with more common maculopathy such as Age-related Macular Degeneration (AMD). To gain insights into pathogenicity of DRAM2-related retinopathy, we used a combination of in vitro and in vivo models. We found that DRAM2 loss in human pluripotent stem cell (hPSC)-derived retinal organoids caused the presence of additional mesenchymal cells. Interestingly, Dram2 loss in mice also caused increased proliferation of cells from the choroid in vitro and exacerbated choroidal neovascular lesions in vivo. Furthermore, we observed that DRAM2 loss in human retinal pigment epithelial (RPE) cells resulted in increased susceptibility to stress-induced cell death in vitro and that Dram2 loss in mice caused age-related photoreceptor degeneration. This highlights the complexity of DRAM2 function, as its loss in choroidal cells provided a proliferative advantage, whereas its loss in post-mitotic cells, such as photoreceptor and RPE cells, increased degeneration susceptibility. Different models such as human pluripotent stem cell-derived systems and mice can be leveraged to study and model human retinal dystrophies; however, cell type and species-specific expression must be taken into account when selecting relevant systems.